Spatial Orientation and Navigation in Children With Perinatal Stroke. Issue 3 (3rd April 2017) - Murias, Kara; Kirton, Adam; Tariq, Sana; Gil Castillejo, Adrian; Moir, Andrea; Iaria, Giuseppe
ABSTRACT: As a focal injury in an otherwise healthy child, perinatal stroke provides a clinical model of developmental brain plasticity. In this study, we report evidence that children with perinatal periventricular venous infarcts perform as well as control children on a video game that tests navigation abilities. In addition, children with a history of perinatal arterial strokes overcame initial deficits in navigation performance after additional practice. These findings lend support to the hypothesis that a complex cognitive skill dependent on a distributed neural network with prolonged maturation, such as navigation, may demonstrate resilience after early brain injury.